Genital Tuberculosis Presenting as Primary Amenorrhoea - Begum, Hamida; Islam, Md Jahidul; Ashrafi, Fatema (Journal of Bangladesh College of Physicians and Surgeons, 2022)
A 23-year-old married woman presented with primary amenorrhoea with well-developed 2ndary sex characteristics. She is chromosomally competent female (46xx) with average body built and had no problem in marital relationship. Clinical examinations and all relevant investigations including transvaginal ultrasound(TVS) showed uterus, adnexa normal size and volume. Progesterone challenge test was negative on 3 occasions. Laparoscopy showed distorted shape of fallopian tubes with beaded appearance. Biopsy from it and endometrial samplzings collected by aspiration showed granuloma with caseation necrosis, typical of tuberculosis (TB) though no AFB found on culture. PCRRFLP also positive for TB. So, primary amenorrhoea with unresponsive endometrium with underlying Genital Tuberculosis was clinical diagnosis. She received 9 months treatments of 4 drugs regimens of anti-TB. J Bangladesh Coll Phys Surg 2022; 40: 302-305